Risk Assessment and Prevention of Malaria Among Italian Troops in Afghanistan, 2002 to 2011. Issue 1 (4th July 2013) - Peragallo, Mario S.; Sarnicola, Giuseppe; Boccolini, Daniela; Romi, Roberto; Mammana, Giacomo
Abstract : Background: Malaria prevention policy is different among coalition troops in Afghanistan, ranging from the combined use of suppressive and terminal chemoprophylaxis to the absence of any prophylactic regimen. The objective of this study was to assess the compliance with malaria prevention measures and the risk of malaria among Italian troops in Afghanistan. Methods: Target population was the cohort of 32, 500 army soldiers deployed in Afghanistan, 2002 to 2011; eligible subjects were the 21, 900 soldiers stationed in endemic areas, who were prescribed mefloquine chemoprophylaxis. Adherence to chemoprophylaxis was assessed by a cross‐sectional study in a volunteer sample of 5, 773 (26.4%) of eligible subjects. The risk of malaria was assessed by detecting malaria cases in the target population. Results: Mefloquine chemoprophylaxis was administered to 4, 123 (71.4%) of the 5, 773 enrolled soldiers and 3, 575 (86.7%) of these took it regularly; however, compliance dropped from 80.9% (2, 592/3, 202) in 2002 to 2006 to 59.5% (1, 531/2, 571) in 2007 to 2011 ( p < 0.01). Adverse events were reported by 875 (21.2%) of the 4, 123 soldiers taking mefloquine, but caused irregularity or interruption of chemoprophylaxis only in 48 (1.2%) and 113 (2.7%) subjects, respectively. No serious adverse events were reported. No malaria cases occurred in Afghanistan, and one Plasmodium vivax case was reported in Italy, yielding an incidence rate of 3.24 cases per 10, 000 person‐months of exposure (1/3, 091) during the transmission season of 2003. Conclusions: In spite of the decreasing compliance with chemoprophylaxis, suggesting a low perception of the risk of malaria, this study confirmed the good tolerability of mefloquine in the military. The risk of malaria for Italian troops in Afghanistan was very low, and chemoprophylaxis was suspended in 2012. A similar policy may be adopted by the generality of International Security Assistance Force troops, and any chemoprophylaxis may be restricted to soldiers stationing in areas where the risk of malaria is substantial.